Hepatoprotective Activity of Hedyotis corymbosa (Linn.) Lam. Extract Against Anti-Tubercular Drug Induced Hepatic Damage in Sprague-Dawley Rats (Bangladesh Pharmaceutical Journal, 2018)
The aim of this study was to investigate the protective actions of hydroalcoholic extract of Hedyotis corymbosa against hepatotoxicity caused by different combinations of anti-tubercular drugs. Antitubercular drugs isoniazid and rifampicin were used to make the elevated level of ALT, AST, ALP and bilirubin as well as decreased level of albumin and total protein. Hepatoprotective activity of the plant was indicated when it causes the decrease of these marker enzymes and elevated level of albumin and total protein. H. corymbosa prevented liver damage caused by anti-tubercular drugs and also from histopathological changes. It can be concluded from the above experiment that hydroalcoholic extract of H. corymbosa showed significant hepatoprotective activity against antitubercular drugs.Bangladesh Pharmaceutical Journal 21(2): 131-138, 2018